(untitled) (Huellas, 2018)
During neo-developmentalism, the emergence of new urban phenomena typical of metropolitan areas has taken place in the interior of Argentina, giving rise to unprecedented scenarios of territorial tension. By using primary and secondary sources, we explore the articulation between the territoriality of tourism, the phenomenon of amenity migration and the urban expansion of mountain tourist destinations with a great demographic growth, through subdivisions and closed housing developments. We also analyze the main socio-geographical impacts generated, such as the clearing of forest areas and the displacement of traditional rural activities. The study area is located in the Conlara Valley, in the province of San Luis, and comprises the localities of Camino de la Costa, Villa de Merlo and Santa Rosa del Conlara.